Taxonomic and biogeographical review of the genus Trechus Clairville, 1806, from the Tibetan Himalaya and the southern central Tibetan Plateau (Coleoptera: Carabidae: Trechini) - Schmidt, Joachim (Zootaxa, 2009)
This paper summarizes the taxonomic and biogeographical knowledge of Trechus species known so far from the Transhimalaya of Central Tibet and from the southern adjacent Tibetan Himalaya of Tibet and Nepal. Nine species groups are proposed, 25 new species as well as three additional new subspecies are described: The species group of Trechus antonini Deuve, 1997, with ten species newly described: T. astrophilus sp. n., T. budhaensis sp. n., T. lama sp. n., T. rarus sp. n., T. religiosus sp. n., T. singularis sp. n., T. tsampa sp. n., T. tseringi sp. n., T. yak sp. n., with an additional subspecies T. yak shogulaensis ssp. n., and T. yeti sp. n., all from South Central Tibet; the monotypic species group of the newly described Trechus chaklaensis sp. n. from South Central Tibet; the species group of Trechus dacatraianus Deuve, 1996, with two species newly described: T. bastropi sp. n., and T. mieheorum sp. n., both from South Central Tibet; the species group of Trechus franzianus Mateu & Deuve, 1979, with four species newly described: T. aedeagalis sp. n. from Far West Nepal, T. eremita sp. n. from West Nepal, T. muguensis sp. n. from West Nepal, and T. sculptipennis sp. n. from Far West Nepal; the monotypic species group of the newly described Trechus rolwalingensis sp. n. from the upper Rolwaling Valley of Central Nepal, with an additional subspecies T. rolwalingensis daldunglana ssp. n. from the lower Rolwaling Valley; the monotypic species group of the newly described Trechus solhoeyi sp. n. from South Central Tibet; the monotypic species group of the newly described Trechus stratiotes sp. n. from north eastern Saipal Himal of Far West Nepal, with an additional subspecies T. stratiotes malikasthana ssp. n. from south eastern Saipal Himal; the species group of Trechus thibetanus Jeannel, 1928, with three species newly described: T. dongulaensis sp. n., T. glabratus sp. n., and T. namtsoensis sp. n., all from South Central Tibet; the species group of Trechus wrzecionkoi Deuve, 1996, with two species newly described: T. korae sp. n., and T. martinae sp. n., both from South Central Tibet. The following two synonymies are proposed: Trechus franzianus Mateu & Deuve, 1979 = Trechus surdipennis Mateu & Deuve, 1979, syn. n.; Trechus thibetanus Jeannel, 1928 = Trechus pseudocameroni Deuve, 1996, syn. n. A key to all species known of South Central Tibet and the Tibetan Himalaya is presented for the first time, and the distributional data of all these species are mapped. The distributional maps highlight the extremely limited distribution of all wingless Trechus species. In situ speciation following the geographical separation of the range of the ancestral species and lack of subsequent range expansion of strictly edaphic species is postulated. Trechus species do not only exhibit a stronger local endemism, but the individual species groups are also endemic to several parts of the Himalayan-Tibetan Orogen. This indicates that the evolution of these Trechus species groups is directly linked to separate geological formations. Based on geological knowledge, the evolution of the species groups endemic to the Tibetan Himalaya and the Transhimalaya started already in the Miocene after these mountains were lifted up to high montane elevations. The recent distributional area of the species can therefore not be the result of range expansion during the Holocene from Pleistocene refugia outside the Tibetan Himalaya or the Transhimalaya. Instead the existence of glacial refugia can be postulated to be in the lower parts of the same mountain slope on which the species occur today. These results clearly challenge the theory of a Tibetan inland ice sheet stretching through the Himalayan transverse valleys during the Last Glacial Maximum.